2005
DOI: 10.1207/s15326942dn2801_5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Parents' Educational Level on the Development of Executive Functions

Abstract: Information about the influence of educational variables on the development of executive functions is limited. The aim of this study was to analyze the relation of the parents' educational level and the type of school the child attended (private or public school) to children's executive functioning test performance. Six hundred twenty-two participants, ages 5 to 14 years (276 boys, 346 girls) were selected from Colombia and Mexico and grouped according to three variables: age (5-6, 7-8, 9-10, 11-12, and 13-14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
225
4
44

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(302 citation statements)
references
References 29 publications
29
225
4
44
Order By: Relevance
“…Socio-economic status is known to confer an executive function advantage (Ardila et al, 2005). The nature of that advantage is difficult to interpret, however, as SES is most likely a proxy for the opportunity to engage in challenging activities that lead to better executive function (Valian, 2015).…”
Section: Other Significant Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Socio-economic status is known to confer an executive function advantage (Ardila et al, 2005). The nature of that advantage is difficult to interpret, however, as SES is most likely a proxy for the opportunity to engage in challenging activities that lead to better executive function (Valian, 2015).…”
Section: Other Significant Factorsmentioning
confidence: 99%
“…Socially advantaged 4-to 7-year-old children have been shown to perform faster than their age-matched peers in terms of accuracy and speed in a flanker task (Mezzacappa, 2004), and parental level of education has been shown to predict children's development of executive functions (Ardila, Rosselli, Matute, & Guajardo, 2005;Merz et al, 2015). A number of studies controlling for SES indeed found no bilingual advantage (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Family income has been shown to negatively predict numerous academic outcomes (Burchinal et al, 2006;Krishnakumar & Black, 2002;McLoyd, 1998) and more recently, behavioral regulation (Evans & Rosenbaum, 2008;Mistry et al, 2010;Raver, Mccoy, Lowenstein, & Pess, 2013;Sektnan et al, 2010;Wanless, McClelland, Tominey, et al, 2011). It has also been established that children whose mothers have low levels of education are more likely to perform poorly on achievement and behavioral regulation tasks (Ardila, Rosselli, Matute, & Guajardo, 2005).…”
Section: Behavioral Regulationmentioning
confidence: 99%
“…Although the latter finding -higher verbal IQ predicting a higher number of visuospatial inhibition errors -may indicate that the application of verbal strategies may be detrimental to performance on some tasks, the possibility that participants were using such strategies, such as verbal self-reminding (Russell, Jarrold, & Hood, 1999) (Noble, McCandliss, & Farah, 2007), level of parental education (Ardila, Rosselli, Matute, & Guajardo, 2005), disciplinary environment (Talwar, Carlson, & Lee, 2009) and the physical characteristics of the home environment (Faber Taylor, Kuo, & Sullivan, 2002). Such variables may also influence the cognitive performance of individuals with genetic syndromes.…”
Section: Limitations and Possible Future Directionsmentioning
confidence: 99%